Interaction of nutrient supply and crop load of apple trees (Malus domestica Borkh.) - Szűcs, E.; Kállay, T. (International Journal of Horticultural Science, 2008)
Long term fertilisation trials were combined with storage experiments with ’Jonathan’ apple trees and fruits to study influence of tree nutrition on quantity and quality of crop. The site of experiments is a typical Carpathian-basin environment with loamy silt soil, high lime content and arid summers. Conclusions has been drown from six years’ set of data. Augmented levels of soil fertilisation increased cropping capacity of apple trees, however, the fruit load has not met with cropping capacity in every year. More the def cit came into view in crop load, less the fruit quality resulted in. The deficit in cropping capacity, however, could not have been determined with simple rates as fruit weight per trunk circumference or similar. Better determination was obtained where foliar nutrient contents were correlated to crop per tree figures. In general terms, the N and Ca content in leaves increased with yields when K and P content formulated reciprocally. When storage quality of ’Jonathan’ apple fruits were related to crop load (kg/tree), influence of crop deficit became visible. As the crop load and foliar nutrient levels interacted, the fruit quality (number of disordered apples after 6 month of storage) subjected of both physiological phenomena. Higher determination degree were obtained when crop load was assessed together with single or multiple foliar analysis data.